Effects of intravenous lipid emulsions on the reversal of pacing-induced ventricular arrhythmias and electrophysiological alterations in an animal model of ropivacaine toxicity. (3rd August 2022) - Zaballos, Matilde; Fernández, Ignacio; Rodríguez, Lucia; García, Sergio; Varela, Olalla; Quintela, Oscar; Anadón, María-José; Almendral, Jesús
Abstract: Introduction: Ropivacaine is considered to have a wider margin of cardiovascular safety. However, several reports of ventricular arrhythmias (VA) due to ropivacaine toxicity have been documented. Intravenous lipid emulsions (ILEs) have recently been used successfully in the treatment of local anesthetic intoxication. The main objective of the present study was to evaluate the efficacy of the ILEs in the prevention of pacing-induced-VA and electrophysiological alterations in an animal model of ropivacaine toxicity. Methods: Nineteen pigs were anesthetized and instrumentalized. A baseline programmed electrical ventricular stimulation protocol (PEVSP) to induce VA was performed. Ropivacaine (5 mg·kg −1 + 100 μg·kg −1 ·min −1 ) followed by normal saline infusion (control group n  = 8) or intralipid 20% (1.5 mL·kg −1 + 0.25 mL·kg −1 ·min −1 ) for the ILE group ( n  = 8), were administered three minutes after the ropivacaine bolus. PEVSP was repeated 25 min after the onset of ropivacaine infusion. Pacing-induced VA and electrophysiological abnormalities were assessed in both groups. A sham-control group ( n  = 3) without ropivacaine infusion was included. Results: Most of the electrophysiological parameters evaluated were affected by ropivacaine: PR interval by 28% ( p  = 0.001), AV interval by 40% ( p  = 0.001), sinus QRS by 101% ( p  = 0.001), paced QRS at a rate of 150 bpm by 258% ( p  = 0.001), and at 120 bpm by 241% ( p  = 0.001). Seven animals (87.5%) in the control group and eight animals (100%) in the ILE group developed sustained-VA ( p  = 0.30). Successful resuscitation occurred in 100% of animals in the ILE group vs. 57% of animals in the control group, p  = 0.038. Pacing-induced-VA terminated at the first defibrillation attempt in 75% of the animals in the ILE group vs. 0% in the control group, p  = 0.01. Conclusion: Ropivacaine strongly altered the parameters of ventricular conduction, thus facilitating the induction of VA. ILEs did not prevent pacing-induced VA. However, facilitated resuscitation and termination of VA were delivered at the first defibrillation attempt compared to the control group.